Strategi Pencegahan Kenakalan Remaja untuk Mewujudkan Generasi yang Sehat dan Berkualitas : Penelitian - M. Faisal Husna; Rahmadi Ali; Rosmilan Pulungan; Andika Prasetia; Five Nadya Selvy; Khasyifa Mahfuzha Anarfy; Miflah Azizah Nasution; Siti Fadila; Ubay Nugroho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity aims to enhance students’ awareness and understanding of juvenile delinquency prevention strategies in an effort to develop a healthy and high-quality generation through the roles of family, school, and society. The activity was carried out in the form of an educational socialization program using lecture, discussion, and question-and-answer methods. The materials presented covered the definition of juvenile delinquency, its types, contributing factors, negative impacts, and prevention strategies applicable in school and family settings. The participants consisted of 29 students from Grade XII MIPA 1 at SMA Swasta Eria Medan. The results indicate an improvement in students’ understanding of the dangers of juvenile delinquency and the importance of self-control and positive peer environments. Active student participation during the sessions reflected a positive response to the program. The prevention strategies emphasized include strengthening character education, improving communication between students, teachers, and parents, and fostering a supportive social environment. This activity concludes that collaboration among family, school, and community plays a strategic role in reducing juvenile delinquency and shaping morally responsible and high quality youth.